Diagnostic and clinical utility of the wireless motility capsule in children: A study in patients with functional gastrointestinal disorders. Issue 4 (12th November 2020) - Rodriguez, Leonel; Heinz, Nicole; Colliard, Kitzia; Amicangelo, Maureen; Nurko, Samuel
Abstract: Background: The wireless motility capsule (WMC) evaluates gastrointestinal motility and transit simultaneously. We evaluated the utility of the WMC in children with functional gastrointestinal symptoms. Methods: Study in children comparing WMC transit and motility parameters between those with upper (UGI) or lower (LGI) gastrointestinal symptoms, nuclear medicine gastric emptying time (NMGET) and/or a colonic radiopaque marker (CROM) study. Key Results: We prospectively recruited 57 children (median age 16.45y, range 8.78‐17.8y, 44 Female) and 50 completed the study (24 UGI/26 LGI). We found no association between WMC study interpretation, motility and transit parameters and symptoms. WMC and NMGET interpretation agreement observed in 24/34 (70%) (κ = 0.351, p  = 0.026) and with CROM in 17/21 (81%) patients (κ = 0.576, p  = 0.007). WMC detected abnormal gastric transit in 41% vs. 24% with NMGET ( p  = 0.04) and abnormal colon transit in 62% vs. 71% of patients by CROM ( p  = 0.01). We found significant correlation ( r  = 0.574, p  = 0.01) and no difference in median colon transit ( p  = 0.421) by WMC and CROM. A single WMC motility parameter, mean peak amplitude, was associated with NMGET ( p  = 0.04), none with CROM. Capsule retention >5 days ( n  = 9, all passed <2 weeks) was associated with prolonged colon transit, not with symptoms, age and gender. Conclusions: WMC is well tolerated in children as young as 8 years old. We found no association between WMC and symptoms, fair agreement with NMGET and strong agreement with CROM. WMC increases the yield of finding gastrointestinal transit abnormalities. Capsule retention in children is associated to prolonged colon transit. Larger studies are needed to further validate these findings. Abstract : Study evaluating the utility of the wireless motility capsule in children with functional gastrointestinal disorders. WMC parameters and interpretation are not associated with symptoms but we found a fair agreement with the gastric emptying by nuclear medicine and a strong agreement with the colonic transit by radiopaque markers. WMC is well tolerated in children as young as 8 years old, and delayed capsule expulsion is associated to prolonged colon transit.